Development of Operational Level Practical Test Instrument by Using Competency-Based Assessment Model - Irwan, Irwan; Sarifuddin, Sarifuddin; Wanda Putra, Riki; Devin, Hasri (Cetta: Jurnal Ilmu Pendidikan, 2024)
The lack relevance of practical ability assessment with industry needs causes nautical technology graduates to not be fully prepared to work in the field. Therefore, it is necessary to develop a practical test instrument that is in accordance with Graduate Learning Outcomes. The purpose of this study is to produce an operational level practical test instrument with a valid, reliable, and effective competency-based assessment model. This type of research is development research by using the Wilson Model and the Oriondo and Antonio Model. Validity test was content validity. Reliability test was test-retest and inter-rater reliability. Effectiveness test used the N-Gain percentage. The results of the study prove that the developed instrument is valid with a validity value 3.8 and criterion A. The instrument is reliable because the t-count value is smaller than the t-table value, meaning that there is no difference between the average values ​​of the three raters. The instrument is effective because the N-Gain percentage = 74.6%. The limitations of this study lie in the limited testing, only focusing on the operational level, and the variation of raters who only come from within the institution. The recommendation from this study is that the developed instrument should be tested in other maritime educational institutions. Then, it is necessary to develop similar instruments for the management level in the maritime sector.